Prevalence and Risk Factors of Hypertension among Male Occupational Bus Drivers in North Kerala, South India: A Cross-Sectional Study - Arjun Lakshman, Neeraj Manikath, Asma Rahim, and V. P. Anilakumari (ISRN Preventive Medicine, 2014)
Background. Hypertension is a leading cause of morbidity and mortality worldwide. We aimed to evaluate the prevalence of hypertension in a population of male bus drivers in North Kerala, India. Methods. The study population included male bus drivers of Corporation Bus stand Kozhikode, Kerala. Blood pressure, height, and weight of subjects were measured, and relevance was obtained using a structured questionnaire. Results. Age varied from 21 to 60 years (mean 36.5 ± 8.4). Among 179 bus drivers studied, 16.8% (30/179) had normal BP, 41.9% (75/179) had prehypertension, and 41.3% (74/179) had hypertension. Isolated systolic HTN was seen in 6.70% (12/179) individuals. Out of 74 hypertensives, 9 (12.1%) were aware of their hypertension, while 3 (4.0%) were medicated and only 1 (1.3%) had BP adequately controlled. Age > 35 years (P = 0.015), BMI ≥ 23 kg/m 2 (P = 0.007), supporting more than four family members (P = 0.011), and taking main meals from restaurants on most working days (P = 0.017) were independently associated with HTN in binary logistic regression. Conclusion. Prevalence of hypertension was high among bus drivers. Age > 35 years, elevated BMI, supporting a large family, and dietary habits associated with the job showed significant association with hypertension. Primary and secondary prevention strategies need to be emphasized in this occupational group.